Current Sanctions Regime Against Russia: Characteristics and Global Aspect - V. V. Arkhipova (Мир новой экономики, 2018)
The paper is devoted to the analysis of actual dynamic sanctions regime established against Russia in 2014 and lasting till nowadays. The subject matter of the research includes the contents of sanctions regime in regard to Russia (national aspect) and the current condition of world financial system and international trade in the context of developing sanctions as an instrument of foreign policy (global aspect). The object in view is to determine the structure and attributes of complex sanctions regime against Russia, identify and estimate its global consequences. In order to measure the global results of Anti-Russian sanctions and countersanctions we implement statistical analysis using the databases of BIS, IMF and INTRACEN during 2011-2016. The detailed classification of sanctions against Russia is also offered. We came to a conclusion that analyzed sanctions regime has strictly negative global outcomes which can be combined into two groups: real (such as diplomatic, negative expectations of economic agents, “lost trade” and “collateral trade damage”, distortion of trade and financial flows through incorporation of additional mediators, manufactured slowdown of global credit market, lack of responsibility for global financial development typical for sender countries) and potential (i. e. origin of new types of “contagion” effect, risks of financial concentration and “bubbles” in global non-credit markets to occur).